Increased wheat grain yield thanks to improved germplasm in spite of climate warming - CGIAR Research Program on Wheat (2021)
Study results show that breeding efforts to produce heat-tolerant wheat not only supports current climate change adaptation but also offer an opportunity to obtain larger, faster genetic gains in future.